Autoethnography and the doctorate in business administration: Personal, practical and scholarly impacts. Issue 2 (July 2019) - Davies, Julie; McGregor, Frances; Horan, Mark
Abstract: Using the Researcher Development Framework (RDF), we analyse autoethnographies in impact statements by doctorate in business administration (DBA) students to understand outcomes for self-reflexivity, management practices, and scholarship. We also use comparative data to content-analyse keywords on UK business school DBA web sites to explore institutional expectations. As a terminal applied research degree, the DBA is designed to generate contextualised 'mode 2' knowledge driven by solving organisational problems within students' own practices. While our paper shows that DBA students value the impact of the DBA journey on themselves as reflective practitioners, only a few web sites expect DBA students to publish. Consequently, we call for greater emphasis on DBA students' potential contributions to academic publications and the growing research impact agenda. We argue that business schools should raise the ambitions of these experienced scholar-practitioners to be more fully integrated into the academy, creating greater synergies between personal impacts, practice and management scholarship in their research. Furthermore, we highlight the value of autoethnography (AE) as a useful method to incorporate self-reflexivity and to map the socialisation of DBA students within the academy. Finally, we recommend collaborative AE for DBA students and their supervisors to evidence personal, practical, and scholarly published impacts. Highlights: DBAs enhance self-reflexivity and management practices. We recommend greater recognition of DBA scholarly publications and wider impacts. Collaborative autoethnography is an interesting option.